Organization of central synapses by adhesion molecules - Tallafuss, Alexandra (Eur J Neurosci, 2010)
Synapses are the primary means for transmitting information from one neuron to the next. They are formed during development of the nervous system, and formation of appropriate synapses is crucial for establishment of neuronal circuits that underlie behavior and cognition. Understanding how synapses form and are maintained will allow us to address developmental disorders such as autism, mental retardation and possibly also psychological disorders. A number of biochemical and proteomic studies have revealed a diverse and vast assortment of molecules present at the synapse. It is now important to untangle this large array of proteins and determine how it assembles into a functioning unit. Here we focus on recent reports describing how synaptic cell adhesion molecules interact with and organize the pre- and postsynaptic specializations of both excitatory and inhibitory central synapses.